Emergency department syndromic surveillance to investigate the health impact and factors associated with alcohol intoxication in Reunion Island. Issue 6 (10th February 2017) - Vilain, Pascal; Larrieu, Sophie; Mougin-Damour, Katia; Marianne Dit Cassou, Pierre-Jean; Weber, Marc; Combes, Xavier; Filleul, Laurent
Abstract : In Reunion Island, alcohol is the most tried out psychoactive substance. To our knowledge, few indicators measuring the health burden of alcohol use exist on the island. In this context, an exploratory analysis based on syndromic surveillance data was implemented in order to describe the emergency department (ED) visits for alcohol intoxication (AI) and factors associated with their variations. An analysis of anonymized records routinely collected by the syndromic surveillance system was carried out. A daily indicator of ED visits for AI was built from a selection of ICD-10 codes between 2010 and 2012. Health impact of AI was first described comparing this indicator to all causes ED visits. Then, AI visits were analyzed with time-series methods using generalized additive Poisson regression models allowing for overdispersion. The following variables were included in the model: long-term trend, seasonality, day of the week, public and school holidays, days of festival and minimum social benefits payday. During the study period, 16 652 visits for AI were recorded in EDs of Reunion Island. AI visits were the second reason for ED visits (i.e. 4%) after traumatism. AI visits mainly concerned men (87%) and the age group of 25-54 years (69%). There was a significant increase in ED visits for AI during days of benefits payday, weekends and publics holidays. This study demonstrated the interest of syndromic surveillance to monitor non-infectious diseases. Time-series models showed a robust association between ED visits for AI and several factors.